1993
DOI: 10.1144/gsl.sp.1993.073.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial scour and incision: models for their influence on the development of realistic reservoir geometries

Abstract: The three-dimensional geometry of fluvial sandbodies may be very complicated. Factors influencing this complexity include the processes of fluvial scour and incision, both of which can promote local or widespread increases in sandbody thickness. Incision, as caused by downstream relative base-level fall, produces entrenched valleys that control the location of subsequent alluvial deposits. A simple model is presented that attempts to quantify the scale of this extrinsic incision and, in turn, highlights severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 73 publications
(46 reference statements)
1
45
0
Order By: Relevance
“…At both traverse ends, this central PI sequence is bounded by grey sands of As-polluted PC aquifers which occupy 40 km of the traverse. The post-LGM channels have not much truncated the PI sequence because their depth of incision has been mostly too shallow to do so, being imposed by decreased base-level gradients (Salter 1993) as sea level rose after 18 ka.…”
Section: Extent Of Low-as Pi Aquifersmentioning
confidence: 99%
“…At both traverse ends, this central PI sequence is bounded by grey sands of As-polluted PC aquifers which occupy 40 km of the traverse. The post-LGM channels have not much truncated the PI sequence because their depth of incision has been mostly too shallow to do so, being imposed by decreased base-level gradients (Salter 1993) as sea level rose after 18 ka.…”
Section: Extent Of Low-as Pi Aquifersmentioning
confidence: 99%
“…10) this problem is reduced with the thickness more likely to correspond to the channel depth, recognizing that 'channel depth as routinely measured and inferred from sedimentary features (i.e. point bars) will be less than total scour depth' (Salter, 1993). It should also be noted that maximum scour and aggradation will tend to produce sandbodies that are thicker than channel depth (Fielding & Crane, 1987;Salter, 1993).…”
Section: Combining Data From Modern Rivers With Outcrop Datamentioning
confidence: 99%
“…point bars) will be less than total scour depth' (Salter, 1993). It should also be noted that maximum scour and aggradation will tend to produce sandbodies that are thicker than channel depth (Fielding & Crane, 1987;Salter, 1993). Despite these caveats, it is suggested that reliable depth estimates from stratasets or storeys can be used to estimate palaeochannel depth, and this estimate can then be used in estimating bar size and distribution from the empirical relationships derived for modern braided rivers.…”
Section: Combining Data From Modern Rivers With Outcrop Datamentioning
confidence: 99%
“…The flashiness of flood hydrographs and the susceptibility of surface sediments to entrainment mean that dryland flows act as non-uniform, non-steady, discontinuous agents of mass sediment transfer. A dryland storm can be thought of as giving rise to a non-synchronised, autogenic scour and fill event, controlled more by local flow conditions than by trends in allogenic stresses (Salter, 1993).…”
Section: The Nature Of Water-lain Dryland Sedimentsmentioning
confidence: 99%